La reparación del daño causado por el delito en el derecho brasileño: evolución histórica - Madlener, Silma Marlice (Revista de Derecho de la UNED (RDUNED), 2015)
La reparación del daño causado por el delito se en¬cuentra regulada en todos los ordenamientos jurídicos. Sin embargo, cabe destacar que el sistema brasileño es uno de los pioneros. En el presente trabajo se hace un estudio de la evolución histórica desde el periodo colonial que se inicia en el siglo xvi hasta la consolidación de la democracia que tiene lugar tres siglos y medio más tarde. Se con¬templa esta institución en los Códigos criminales brasileños, su con¬solidación en el ámbito civil; periodos republicanos y su encaje en las Constituciones. En conjunto se destaca como el sistema ha ido perfeccionándose a lo largo de ese ese extenso periodo de tiempo que supera los trescientos años. There is a long tradition in Brazilian legislation to guarantee compensation for the damage caused by crimes. A interesting idea is that in the bill for a Penal Code of Vasconcellos in the Year 1827. The idea was to have a public found to pay the compensation to the victims in all cases. The code of 1830, the first Brazilian Criminal Code, was very progressiv, under the influence of Jeremy Bentham: The payment of damages was considered as an obligation under «droit publique». Annother important advance is found in the Draft Penal Code of Sá Pereira 1933. It provides seizure of proceeds of crime, and the judge can use part of it for compensation of the victim. In the Draft of Alcântara Machado in 1938 a found for the victims was provided, more than 100 years after Vasconcellos had proposed it. (1827). The Penal Code of 1940 treated the compensation under the heading «penal sanctions» («das penas»). In the Draft Penal Code of 1981 was embodied the idea of the «multa reparatória», which should serve the the victim’s compensation, but was not accepted in the new General Part Penal Code in 1984.